Rules of the house - Barnett, Mac; Myers, Matthew, 1960- (Los Angeles ; New York : Disney * Hyperion Books, 2015)
Ian always follows the rules and his sister, Jenny, never does but when she angers some monsters while breaking all the rules of their vacation house in the woods, Ian first runs away, then realizes there should be a rule about protecting your sister from being eaten by monsters.
Keywords: Rules (Philosophy) -- Fiction; Brothers and sisters -- Fiction; Monsters -- Fiction